Sequential dual site-selective protein labelling enabled by lysine modification. Issue 22 (15th November 2020) - Matos, Maria J.; Brown, Libby; Bernardim, Barbara; Guerreiro, Ana; Jiménez-Osés, Gonzalo; Bernardes, Gonçalo J.L.
Graphical abstract: Abstract: Methods that allow for chemical site-selective dual protein modification are scarce. Here, we provide proof-of-concept for the orthogonality and compatibility of a method for regioselective lysine modification with strategies for protein modification at cysteine and genetically encoded ketone-tagged amino acids. This sequential, orthogonal approach was applied to albumin and a therapeutic antibody to create functional dual site-selectively labelled proteins.